Failed States:: Why They Matter and What We Should Do about Them - Fraser, Derek (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2008)
ABSTRACT Failed states are usually defined as those that are unable effectively to control their territory and comply with their international obligations. As such, they often pose a threat to their own populations and to international security. Failed states are of increased concern to Canadians, both because of the new UN doctrine of the "Responsibility to Protect," and because their threat to international security has been increased by the effects of global integration. In addition, the very process of globalization, coupled with the effects of climate change, may cause their numbers to grow. The cost of resuscitating a failed state, however, is so considerable that, where we can prevent them from occurring, we should do so. The difficulties faced by the United States in Iraq and by the international community in Afghanistan, should not obscure the fact that since the end of the Cold War the world has been largely successful in reducing the number of armed conflicts arising from state failure. Since the problem of failed states may get worse, and in any case is not going away, we likely cannot lessen, and may have to increase our efforts to respond to the threats they pose. To do so adequately, however, will require governments to maintain public support for such missions. The growing public dissatisfaction with Canadian intervention in Afghanistan makes it clear how difficult this can be. A key factor in keeping public backing would be to agree to take part in peace-building missions only under appropriate conditions, following a debate in parliament.